2019
DOI: 10.1111/ipd.12506
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of child physical abuse by a group of Brazilian primary care health professionals

Abstract: Background Child maltreatment is a complex social and public health problem. Aim To evaluate the frequency of the recognition by Brazilian health professionals in primary care of child physical abuse (CPA) and associated factors. Design A representative cross‐sectional study was conducted with dentists, nurses, family physicians, and pediatricians who participated in the network of the Family Health Strategy in the city of Belo Horizonte, Brazil. Data collection involved in the administration of a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 27 publications
3
13
0
2
Order By: Relevance
“…A survey conducted in Northern Ireland with primary heathcare workers showed that dentists were the professionals with the highest underreporting rates 24 . These findings are in line with some studies that found a low number of cases of child abuse reported by dentists 2,25,16,27 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A survey conducted in Northern Ireland with primary heathcare workers showed that dentists were the professionals with the highest underreporting rates 24 . These findings are in line with some studies that found a low number of cases of child abuse reported by dentists 2,25,16,27 .…”
Section: Discussionsupporting
confidence: 92%
“…By looking at the high rate of non-reporting behavior observed in the present study and in similar studies carried out with health professionals 14,16,25,31 , one perceives the need of further investigation into the factors related to these low reporting rates that could provide clearer evidence and contribute to the debate on this topic, allowing for new measures and public policies for the prevention of child abuse and for the health support of children and adolescents.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Apesar de uma boa parcela da amostra se considerar de certa forma capaz de identificar MTI, corroborando com os achados de Azevedo et al (2012) 32 , outros estudos demonstram que existe subnotificação dos casos por profissionais de saúde, o que pode expor a existência de uma lacuna entre a identificação dos casos e sua notificação 8,[32][33][34][35][36] . Mesmo considerando-se capaz de identificar um caso suspeito, muitos CD não sabem como proceder.…”
Section: Discussionunclassified